The Other Side of Language: A Philosophy of Listening - Fiumara, Gemma Corradi (London Routledge, 1990)
We are inhabitants of a culture that knows how to speak but not how to listen. Against a tradition that has endorsed the power of discourse, where warring monologues are mistaken for genuine dialogue, Gemma Corradi Fiumara examines and reveals the other side of language - listening.
Keywords: Philosophy; Linguistics; Listening